DIGITAL HUMANISM IN THE AGE OF THE INTERNET AND ARTIFICIAL INTELLIGENCE: CHALLENGES, OPPORTUNITIES, AND PROSPECTS FOR DEVELOPMENT - Mykyta Slyusar; Vitaliia Nikitenko; Valentyna Voronkova (Baltic Journal of Economic Studies)
The relevance of this research topic lies in the evolving nature of digital humanism, a multifaceted and complex process aimed at achieving an optimal balance between the advancement of digital technologies and the preservation of human values and dignity. The study seeks to identify the conditions necessary for the conceptualisation of digital humanism in the era of artificial intelligence, and to analyse the challenges and opportunities associated with its development. The following research objectives are proposed: firstly, to clarify the essence, characteristics, and developmental trajectories of the concept of digital humanism; secondly, to examine the transformation of digital humanism in the context of the internet and artificial intelligence; thirdly, to establish the concept of digital humanism as a framework for harmonising technological advancement with the preservation of human potential; and finally, to explore cultural diversity as an embodiment of digital humanism and human values. Methodology. The study uses systemic, cross-cultural, axiological, anthropological and interdisciplinary approaches to provide a comprehensive analysis of digital humanism, facilitating an understanding of the interaction between digital technologies and humanity. A review of the literature shows that in the age of the Internet and artificial intelligence, digital humanism needs to be integrated into practical domains. This interdisciplinary research brings together philosophical, sociological, ethical and computer science perspectives to examine digital humanism in this transformative era. Artificial intelligence has opened up groundbreaking possibilities in fields such as medicine, education, transport and commerce. The study also highlights the European Digital Humanism Initiative and the methodology of informationalism, which illuminate the challenges and opportunities of digital humanism. Anthropological and socio-axiological approaches are used to analyse the value dimensions of the digital society, focusing on its impact on education, knowledge diffusion and innovation. Findings and implications. The results obtained provide a more profound comprehension of the genesis and pertinence of digital humanism in the context of societal transformation. This research underscores its capacity to address contemporary challenges while ensuring a harmonious coexistence of technological progress and human-centric values.